Binnnig data‐bliss or bane. (6th November 2022) - Thorp, John
Abstract : Deputy Editor‐in‐Chief, John M. Thorp Jr., discusses his main topic in an audio podcast available at: https://soundcloud.com/bjog/December‐editorial‐2022